Riba Free Financing Based On Rental Business - Suhannisah Oktaviany; Pepi Idayanti Marpaung; Dewi Maharani Ginting (Proceeding International Seminar of Islamic Studies, 2019)
Leasing is a financing activity in the form of providing capital goods either on a lease basis with an option rights (financial lease) or a lease without an option right (operati lease) to be used by the lessee (lease) for a Certain period based on payment in a manner Periodically. Leasing financing techniques are divided into two types of leasing transactions items, namely finance lease and operating lease. Indonesia that is commonly done and applied to finance companies is financial lease.